Mathematics anxiety: a bibliometrix analysis / Kartini Kasim ... [et al.] - Kasim, Kartini; Muhd Irpan, Hamidah; Ibrahim, Noorazilah; Abdul Rashid, Nurazlina; Ahmad, Anis Mardiana (2021)
Mathematics anxiety is defined as a feeling of tension and apprehension that interferes with math performance ability, the manipulation of numbers and the solving of mathematical problems in a wide variety of ordinary life and academic situation. In this study, a bibliometric analysis are used to evaluates the mathematics anxiety. Through the use of bibliometrix, this paper investigates the amount of studies conducted in the field of mathematics anxiety, identify the development status and the leading trends in term of publication, document types, cited document, authors and production countries. This study intended to fill a gap in the range of bibliometric studies on mathematics anxiety produced to date, which have been concentrated in only a few publications, and for the part have approached the issues in a general manner. The analysis and the graphical presentation can help both researchers and practioners to better understand the state of the art of mathematics anxiety.